A Luta contra a “Subjugação da Vontade”: Segunda Natureza, Paradoxo da Libertação e Crítica Imanente nas Grundlinien (Revista Eletrônica Estudos Hegelianos, 2021)
In this paper I try to show, first of all, that in Hegel’s philosophy of spirit and second nature theory, freedom means the very dynamic of liberation of the will understood as a process constitutively marked by contradiction and struggle; liberation which, however, while it is understood in this way, leads to the paradox that the act of liberation only becomes possible if the subject’s will is already free or has the feeling of freedom. This paradox can be mitigated when one considers Hegel’s account of cultural maturation process [Bildung] and deepening of the intellectualist concept of critique of the Enlightenment, insofar as he relates it not to mere negation, but to the very "negative side" of the spirit present in the affections, language, memory, history, and praxis that as such are the indices for the spirit of the domination of the will, as e.g. in feelings of fear, disrespect, or invisibility, and as such already the first step on the path to its overcoming. In the second part of the paper I present and discuss some criticisms that have been directed at the Hegelian notion of immanent critique by the first generation of the Critical Theory tradition.